THE OVERDAMPING’S NEGATIVE INFLUENCE TO THE LAND’S PRODUCTIVITY IN THE SOUTH EUROPEAN PART OF RUSSIA - A. Ya. GLUSHKO; V. V. RAZUMOV; M. D. REIJKHANY (Юг России: экология, развитие, 2015)
The land’s overdamping is widly spread on the large territory of the South European part of Russia. Danger of this nature phenomenon is in a worsening of land’s quality and reduction of it’s cadastral value. The land’s overdamping gives warning at the agricultural potential of the South Federal Region by inficting damage to the Region’s economy.